An analysis of Afar pastoralism in the northeastern rangelands of Ethiopia - Helland, J. (International Livestock Centre for Africa, 1980)
Description of the geographical aspects, sociological aspects and administrative aspects of the Afar pastoralists in relation to the Northeast Rangelands Development Project. Data on human population, animal population and pastoral activities; incl. a proposed model of Afar livestock ownership and husbandry systems, and pattern of trade with neighbouring agriculturalists.